The Application Of Simple Learning Strategies To Improve Students' Understanding Of The Present Continuous Tense And Present Perfect Tense: Penelitian - Zahra Meida Lutfiah; Eva Betty Simanjuntak; Elisa Rohali Hasibuan; Christin Novstasya Saragih; Elisabeth Nopianty S; Rosa Caecilia Sitangggang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The ability to understand grammar is an essential foundation in the English learning process, especially at the elementary level. Among the various forms of tense, Present Continuous and Present Perfect are often the main difficulties for elementary school students due to the complexity of their structure and the meaning of time. This study aims to examine in depth the application of simple and contextual learning strategies in improving students' understanding of the two types of tenses. With a descriptive-qualitative approach, the research was carried out through observation, teacher interviews, and the distribution of questionnaires to grade V students at SD Negeri 067694. The results showed that strategies that combined hands-on practice, contextual approaches, and the use of game media such as Tenses Box were able to increase students' participation, comprehension, and enthusiasm in learning grammar. This study recommends the application of active and meaningful learning approaches as an alternative solution to the limitations of traditional teaching models that tend to rely on memorization.